Edukasi Pembuatan Desain Grafis Menarik Menggunakan Aplikasi Canva - Lilis Widayanti; Adriani Kala’lembang; Widya Adhariyanty Rahayu; Suastika Yulia Riska; Yudistira Arya Sapoetra (LP2M Institut Teknologi dan Bisnis Asia Malang, 2021)
One of the capabilities that need to be updated in the era of the COVID-19 pandemic is the ability to utilize technology to disseminate information and communication. In disseminating information, it is necessary to have a media that supports the delivery of information, one of which is design media. Canva is a graphic design application that can help design, create, and edit designs for beginners. These designs can be in the form of greeting cards, posters, brochures, infographics, and even presentations. The service is carried out in partnership with the Mahardika Vocational School of Karangploso. The training material on designing using Canva is focused on poster design. This activity takes place with the transfer of knowledge and technology in the form of Canva training in designing more attractive posters. There are three sessions in the training, an introduction and understanding session, an implementation session, and a training simulation session. The training is carried out through online meetings using the Zoom Meeting application. The training was attended by 27 participants who were students of the Mahardika Vocational School of Karangploso. The evaluation results obtained from the google form score showed an average score of 8.4. These results indicate a positive response from the participants